HUBUNGAN TINGKAT KEPARAHAN PENYAKIT SERTA TINGKAT STRES TERKAIT PSORIASIS TERHADAP TERJADINYA DISFUNGSI SEKSUAL PADA PENDERITA PSORIASIS - , dr. Indri Yulia Rahardani ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Psoriasis is a chronic relapsing disease that can affect physical, psychological and social function on patients. Psoriasis has had a significant impact on sexual function. The aim of the present study is to elaborate the role of demographic factors such as age, sex, duration of illness, onset of illness, genital lesion, joint pain